Pola Pengembangan Sumber Daya Manusia dalam Penanganan Stunting di Wilayah Kerja Puskesmas Maiwa sebagai Lokasi Khusus Stunting Kabupaten Enrekang - Nurmiati Muchlis; Haeruddin Haeruddin; Nurul Susanti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Enrekang Regency is an area with quite a lot of stunting specific locations compared to several other districts in South Sulawesi. The purpose of this study was to analyze the pattern of human resource (HR) development in handling stunting in the work area of the health centers in Enrekang Regency. This research was carried out with a qualitative approach. The informants consisted of the head of the health office, and the head of each health center in the research location. Other informants were health cadres in two health centers working areas. Data were collected through observation, interviews and document studies. The results of the study indicate that the budget for stunting reduction is through BOK funds of health center. The existing budget will be distributed to all health centers in the Enrekang Regency area. HR development costs which consist of selection and recruitment costs as well as training and development costs are charged to the stunting BOK budget. Efforts to develop human resources for dealing with stunting include: training for cadres to accompany pregnancy; training of health cadres for early detection of stunting in toddlers; training to strengthen nutrition package interventions (supplementary food, vitamin A, blood-added tablets) for pregnant women and toddlers; training on monitoring the nutritional status of children under five; formation and training of nutrition post cadres; community training for smart mothers to prevent stunting; as well as the formation and training of occupational health business post cadres. There is no promotion stage because the contract staff's career development only lasts for a year. The available funds may not be used to finance capital expenditure activities, maintenance of buildings, vehicles, facilities and infrastructure, curative and rehabilitative activities, procurement of drugs, vaccines and medical devices.Keywords: stunting; handling; development pattern; human resourcesABSTRAK Kabupaten Enrekang merupakan daerah dengan lokasi khusus stunting yang cukup banyak dibanding beberapa kabupaten lain di Sulawesi Selatan. Tujuan penelitian ini adalah menganalisis pola pengembangan sumber daya manusia (SDM) dalam penanganan stunting di wilayah kerja Puskesmas di Kabupaten Enrekang. Penelitian ini dilaksanakan dengan pendekatan kualitatif. Informan terdiri dari kepala dinas kesehatan, dan masing-masing kepala puskesmas di lokasi penelitian. Informan lainnya yaitu kader kesehatan di dua wilayah kerja puskesmas. Data dikumpulkan melali observasi, wawancara dan studi dokumen. Hasil penelitian menunjukkan bahwa anggaran penurunan stunting melalui dana BOK puskesmas. Anggaran yang ada akan distribusikan untuk seluruh puskesmas di wilayah Kabupaten Enrekang. Biaya pengembangan SDM yang terdiri atas biaya seleksi dan rekrutmen serta biaya pelatihan dan pengembangan dibebankan pada anggaran BOK stunting. Upaya pengembangan sumber daya manusia penanganan stunting berupa: pelatihan kader pendamping kehamilan; pelatihan kader kesehatan deteksi dini stunting pada balita; pelatihan penguatan intervensi paket gizi (pemberian makanan tambahan, vitamin A, tablet tambah darah) pada ibu hamil dan balita; pelatihan pemantauan status gizi balita; pembentukan dan pelatihan kader pos gizi; pelatihan komunitas ibu cerdas cegah stunting; serta pembentukan dan pelatihan kader pos usaha kesehaan kerja. Tidak ada tahapan promosi karena dalam pengembangan karier tenaga kontrak hanya berlangsung hanya selama setahun. Dana yang tersedia tidak boleh dimanfaatkan untuk membiayai kegiatan belanja modal, perawatan bangunan, kendaraan, sarana dan prasarana, kegiatan kuratif dan rehabilitatif, pengadaan obat, vaksin dan alat kesehatan.Kata kunci: stunting; penanganan; pola pengembangan; sumber daya manusia